MENENGOK KELEMAHAN PERFILMAN INDONESIA - Elsha, Debby Dwi (Jurnal Ilmu Komunikasi AKRAB, 2017)
AbstractFilm is one mass media that produces massively popular culture. Film can be a mass media that effectively conveys messages to the public. As a creative product that the public interest, the film is able to introduce Indonesian culture to the world. The income of the film industry can contribute greatly to the state income. The condition of the film industry in Indonesia is still strongly influenced by imported films that have better narrative and cinematic qualities than domestically made films. To be in control of the domestic film industry, there needs to be an improvement in order to compete in the international film industry. This study describes the weaknesses of the Indonesian film industry from the aspects of production, distribution, exhibition and consumption. In addition to the lack of quality Indonesian film technically, there needs to be an evaluation and improvement of the distribution system in order to distribute the film widely even throughout the world. The lack of number of cinema screens in Indonesia is also a major factor in blocking access to watch so that the distribution of cinema facilities to all over the country is needed in the short-term future. To improve the skills of human resources requires the education of film disciplines that support the competence of each field. The tastes and needs of the audience also need to be noted so that the film producers can continue to produce quality and varied films. Government support is needed for the Indonesian film industry to compete with overseas so as to promote the film as a creative economic product and represent the image of Indonesian culture in the international film industry.Keywords: film, industry, production, media, creative.